A reescrita de textos na escola: trabalhando com gêneros e sequências didáticas - Lima, Paulo da Silva (2014)
The present work aims at researching the interactive correction in the teaching of writing, focusing on a list of findings as a parameter in the assessment process. Our objective is to demonstrate that this form of intervention in school texts can provide an opportunity of dialogue between students and teachers, as well as offer students guidance on micro and macro-textual issues. In order to achieve our goal, we developed two teaching sequences directed to two genres of students´ writings: school essays and reviews, seeking to provide a real situation of verbal interaction. The subject addressed in the essays was the reduction of criminal responsibility and the theme of the review was the film "Dead Poets Society" (1989). When the project was concluded the students´ texts were shown in and outside school. Bronckart´s theory of text (2007) and the studies of Dolz and Schneuwly (2010) regarding the didactisation of genres were the basis of our investigation. Our work was conducted with students at a public high school, in which we analyzed the linguistic / discursive skills. In doing so, we firstly found out that there was an evolution between the first and last students´ text production, and secondly, that interactive correction educates the student about the importance of rewriting to accomplish a more proficient text production. Furthermore, the interactive intervention helped students to internalize both, the fundamental characteristics and the social-communicative functions of the genre.